Cloning and prokaryotic expression of rice gene encoding β-caryophyllene synthase and its genetic transformation - GE Lin-quan; ZHOU Guo-xin; WANG Qi; ZHU Shu-de; LOU Yong-gen (浙江大学学报. 农业与生命科学版, 2009)
To elucidate the role of β-caryophyllene emitted from rice plants in mediating interactions among rice, herbivores and their natural enemies, a rice β-caryophyllene synthase gene OsCAS was cloned, expressed in E. coli and over-expressed or silenced in rice plants using an Agrobacterium-based transformation system. The gene OsCAS, a 1731 bp cDNA, contains an open reading frame of 1728 bp, which encodes a protein of 576 amino acids with a calculated molecular weight of 66.5 kDa. Phylogenetic tree analysis showed that the putative rice OsCAS had a high amino acid identity (99%) to maize (Zea mays) β-caryophyllene synthase, whereas a low amino acid identity (51%) to those in other plants including Arabodopsis (Arabidopsis thaliana), Artemisia (Artemisia annua) and cucumber (Cucumis sativus). Infestation by rice brown planthopper Nilaparvata lugens (Stål) or jasmonic acid treatment enhanced significantly the expression levels of OsCAS gene. The recombinant OsCAS protein was expressed in E. coli and rice lines with over-expression or RNAi silencing of OsCAS gene were obtained by A grobacterium-mediated transformation, which laid a foundation for elucidating the biochemical and ecological functions of OsCAS.